2023
DOI: 10.1111/nph.19251
|View full text |Cite
|
Sign up to set email alerts
|

The AP2/ERF transcription factor PtoERF15 confers drought tolerance via JA‐mediated signaling in Populus

Lingfei Kong,
Qin Song,
Hongbin Wei
et al.

Abstract: Summary Drought stress is one of the major limiting factors for the growth and development of perennial trees. Xylem vessels act as the center of water conduction in woody species, but the underlying mechanism of its development and morphogenesis under water‐deficient conditions remains elucidation. Here, we identified and characterized an osmotic stress‐induced ETHYLENE RESPONSE FACTOR 15 (PtoERF15) and its target, PtoMYC2b, which was involved in mediating vessel size, density, and cell wall thickness in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…The number of cambium cell layers between internodes was one or two fewer under the drought conditions compared to the control conditions (Figure 2b). These results are consistent with previous studies of xylem in Populus tomentosa [62] and cambium in P. trichocarpa [63].…”
Section: Discussionsupporting
confidence: 94%
“…The number of cambium cell layers between internodes was one or two fewer under the drought conditions compared to the control conditions (Figure 2b). These results are consistent with previous studies of xylem in Populus tomentosa [62] and cambium in P. trichocarpa [63].…”
Section: Discussionsupporting
confidence: 94%
“…The AP2 / ERF transcription factor family is one of the largest transcription factor families in plants, and plays an important role in plant growth and response to stress [ 10 , 35 , 36 , 37 ]. Kong et al [ 38 ] proved that overexpression of PtoERF15 contributed to stem water potential maintenance in response to water deficit in Populus tomentosa , thus promoting drought tolerance. Similarly, Li et al [ 39 ] revealed that overexpression of AtruDREB28 increased tolerance to drought stress by enhancing reactive oxygen species-scavenging capability in Acer truncatum .…”
Section: Discussionmentioning
confidence: 99%
“…CoDREB-11, CoDREB-14, and CoRAV-01 genes were significantly up-regulated under salinity and drought stress conditions. Kong et al [96] demonstrate that the osmotic stress-induced PtoERF15 and its target gene PtoMYC2b, which is involved in mediating blood vessel size, density, and cell wall thickness in response to drought in poplar, were identified and characterised. Overexpression of PtoERF15 contributes to the maintenance of stem water potential, thereby increasing drought tolerance.…”
Section: Ap2/erf Transcription Factors In Response To Drought Stressmentioning
confidence: 99%